Regional variations of mesospheric gravity-wave momentum flux over Antarctica - P. J. Espy; R. E. Hibbins; G. R. Swenson; J. Tang; M. J. Taylor; D. M. Riggin; D. C. Fritts (Annales Geophysicae, 2006)
Images of mesospheric airglow and radar-wind measurements have been combined to estimate the difference in the vertical flux of horizontal momentum carried by high-frequency gravity waves over two dissimilar Antarctic stations. Rothera (67° S, 68° W) is situated in the mountains of the Peninsula near the edge of the wintertime polar vortex. In contrast, Halley (76° S, 27° W), some 1658 km to the southeast, is located on an ice sheet at the edge of the Antarctic Plateau and deep within the polar vortex during winter. The cross-correlation coefficients between the vertical and horizontal wind perturbations were calculated from sodium (Na) airglow imager data collected during the austral winter seasons of 2002 and 2003 at Rothera for comparison with the 2000 and 2001 results from Halley reported previously (Espy et al., 2004). These cross-correlation coefficients were combined with wind-velocity variances from coincident radar measurements to estimate the daily averaged upper-limit of the vertical flux of horizontal momentum due to gravity waves near the peak emission altitude of the Na nightglow layer, 90km. The resulting momentum flux at both stations displayed a large day-to-day variability and showed a marked seasonal rotation from the northwest to the southwest throughout the winter. However, the magnitude of the flux at Rothera was about 4 times larger than that at Halley, suggesting that the differences in the gravity-wave source functions and filtering by the underlying winds at the two stations create significant regional differences in wave forcing on the scale of the station separation.